Dual contraceptive use among women living with HIV on anti-retroviral therapy in Boset district, Ethiopia - Belachwe, Yohanes Abera; Sento, Midekso; Gobena, Melese Negash; Getahun, Mihiret Shawel; Negussie, Yohannes Mekuria (Frontiers in Global Women's Health, 2025)
BackgroundThe World Health Organization advocates dual contraceptive methods for women with Human Immunodeficiency Virus (HIV) to prevent unintended pregnancies and sexually transmitted infections (STIs), enhancing education, economic opportunities, and maternal-child health outcomes. However, persistent global challenges stem from inadequate use of dual contraceptives and unsafe sexual practices, resulting in high rates of unintended pregnancies and significant health risks. Hence, this study aimed to assess dual contraceptive use among women living with HIV on anti-retroviral therapy (ART) in Boset District, Ethiopia.MethodA facility-based cross-sectional study was conducted among 342 women living with HIV from September 12 to October 18, 2023. Participants were selected by systematic random sampling, and data were collected using an interviewer-administered structured questionnaire. The collected data were entered using Epi Info version 7.2.6 and analyzed using SPSS version 26.0. Bivariable and multivariable binary logistic regression analyses were performed to assess the association between the outcome and explanatory variables. In the multivariable analysis, an adjusted odds ratio (AOR) with a 95% confidence interval (CI) was used to show the strength of the association, and the level of significance was set at a p-value of <0.05.ResultsThe magnitude of dual contraceptive use was 33.7% (95% CI: 28–40). Urban residence (AOR = 2.5; 95% CI: 1.97–8.08), good knowledge about dual contraceptives (AOR = 3.8; 95% CI: 2.36–8.67), STIs history in the past 12 months (AOR = 2.6, 95% CI: 1.25–4.72) and having two or more number of sexual partners, (AOR = 1.9; 95% CI: 1.18–6.68), were factors significantly associated with dual contraceptive use.ConclusionOne-third of women living with HIV on ART utilized dual contraceptives. Place of residence, knowledge about dual contraceptives, history of STIs in the past 12 months, and number of sexual partners were factors associated with dual contraceptive use. It is essential to implement focused educational programs to increase knowledge about dual contraceptives, alongside expanding access to contraceptive services in rural and underserved areas.